Thermal conductivity and thermal diffusivity of cores from a 26 meter deep borehole drilled in Livingston Island, Maritime Antarctic - Correia, A. (2012)
During the month of January of 2008 a borehole (Permamodel-Gulbenkian 1 — PG1) 26 m deep was drilled on the top of Mount Reina Sofia (275 m a.s.l.) near the Spanish Antarctic Station of Livingston Island, South Shetland Islands. Cores from 1.5 m to about 26 m deep were collected for measuring several physical properties. The objective of the present work is to report the values of the thermal conductivity and the thermal diffusivity that were measured in the cores from the borehole and the heat production that was estimated for the geological formations intercepted by it. Seven cores were selected to measure the thermal conductivity and the thermal diffusivity. The measured values for the thermal conductivity vary from 2.6 W/mK to 3.3 W/mK while the measured values for the thermal diffusivity vary from 1.1 × 10− 6 m2/s to 1.6 × 10− 6 m2/s. Both thermal conductivity and thermal diffusivity, on average, show a slight increase with depth. Average heat production was also estimated for two portions of the borehole: one from 2 to 12 m and the other from 12 to 25 m. A gamma-ray spectrometer was used to estimate the concentrations of uranium, thorium, and potassium of the cores, from which the heat production per unit volume was calculated. The estimated heat production for the first half of the borehole is 2.218 μW/m3 while for the second half it is 2.173 μW/m3; these heat production values are compatible with acidic rock types. Porosity and density were also estimated for the same cores.